2021
DOI: 10.30892/gtg.38404-738
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Pushing and Pull Factors on Tourist Satisfaction and Return Intention Towards River Tourism in Can Tho City, Vietnam

Abstract: This study was conducted to demonstrate the impacts of push and pull factors on tourist satisfaction and behavioural intention of visitors towards Can Tho City river tourism. Structural Equation Modeling (SEM) was used to analyse the data. Research data were collected by direct interviews with 235 visitors who have experienced the river tour in Can Tho City. The research has shown that push and pulls factors positively affect destination satisfaction. Besides, destination satisfaction promotes the return inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…This indicates that if tourists highly evaluate the service quality, their intention to revisit national parks will be higher. The research results have shown that tourist satisfaction plays a crucial role in the success of the tourist destination (Kozak and Rimmington, 2000) as it influences the intention to revisit the tourist destination (Nguyen and Mai, 2021). In the field of tourism, these research findings align with studies proposed by Carla et al (2017), Loi et al (2017), An et al (2019), Soonsan and Sukahbot (2019), Atmari and Putri (2021), Ćulić et al (2021), Chin et al (2022), Libre et al (2022), Hermann and Nemaorani (2023) and Shatnawi (2023).…”
Section: Discussionsupporting
confidence: 79%
“…This indicates that if tourists highly evaluate the service quality, their intention to revisit national parks will be higher. The research results have shown that tourist satisfaction plays a crucial role in the success of the tourist destination (Kozak and Rimmington, 2000) as it influences the intention to revisit the tourist destination (Nguyen and Mai, 2021). In the field of tourism, these research findings align with studies proposed by Carla et al (2017), Loi et al (2017), An et al (2019), Soonsan and Sukahbot (2019), Atmari and Putri (2021), Ćulić et al (2021), Chin et al (2022), Libre et al (2022), Hermann and Nemaorani (2023) and Shatnawi (2023).…”
Section: Discussionsupporting
confidence: 79%
“…The attitude of local residents towards tourism development is of utmost importance, particularly positive support from them as a significant factor for successful tourism development (Nunkoo and So, 2016;Erul et al, 2020). The presence of local residents in tourism activities plays a vital role that determining the quality of tourism services and enhancing the image of the tourism destination (Thong, 2019;Nguyen and Mai, 2021). Some researchers have argued and demonstrated the positive impact of local residents on the attractiveness of a tourism destination (Zhou, 2005;Quyen and Thao, 2017;Thong and Phung, 2021;Giang, 2022).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The local characteristic scale (4 observed varia bles) was preferenced from studies of Thanh andHa (2021), andSon et al (2023) with 4 observed variables. The satisfaction scale (4 observed variables) was referenced from studies by Mai et al (2021), and Nguyen and Mai (2021). All scales in the research model were measured using a 5-point Likert scale ranging from Strongly Disagree (1) to Strongly Agree (5).…”
Section: Research Scalementioning
confidence: 99%
“…Tourism is one of the fastest-growing industries globally, playing a crucial role in the economy (Osman and Sentosa, 2013), contributing positively to the economic, social, cultural, and international integration processes of Vietnam (Hong et al 2022). Alongside the rapid development of the tourism industry, competition among tourist destinations has become increasingly fierce (Nguyen and Mai, 2021). The success of tourist destinations is often gauged through tourist satisfaction (Kozak and Rimmington, 2000;Nowacki, 2009).…”
Section: Introductionmentioning
confidence: 99%